Saving after retirement and preferences for residual wealth - Giulio Fella; Martin Blomhoff Holm; Thomas Pugh (Bank of Canada, 2024)
We use administrative data for Norway to estimate an incomplete-market life cycle model of retired singles and couples with a bequest motive, health-dependent utility, and uncertain longevity and health. We allow the parameters of the bequest utility to differ between households with and without offspring. Our estimates imply a very strong utility of residual wealth (bequest motive), in line with the estimates by Lockwood (2018). The bequest motive accounts for approximately three-quarters of aggregate wealth at age 85. More surprisingly, we estimate similar utility of residual wealth for households with and without offspring. We interpret this as suggestive evidence that the utility of residual wealth represents forces beyond an altruistic bequest motive.
Keywords: D11; D12; D14; E21; 330; Economic models; Fiscal policy; Housing; Labour markets